2022
DOI: 10.1007/s10880-022-09849-w
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health in Multiple Sclerosis During the COVID-19 Outbreak: A Delicate Balance between Fear of Contagion and Resilience

Abstract: The current study aimed at exploring the relationship between objective disability, illness perceptions, resilience, fear of COVID-19, and psychological distress (i.e., anxiety, depression, and stress) in people with multiple sclerosis (pwMS) during the second wave of the COVID-19 outbreak. A group of 122 pwMS recruited in an Italian university hospital took part in this cross-sectional monocentric study. Hierarchical multiple linear regression analyses were performed to assess the strength of the hypothesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Multiple sclerosis (MS) is a chronic neurodegenerative disease that affects the motor and cognitive systems, increasing the risk of developing negative mental health outcomes, such as depressive symptoms [ 1 , 2 , 3 , 4 , 5 ]. To this end, previous research has found that approximately 25–50% of people with MS (pwMS) have some form of major depression [ 6 ] and that the higher the level of disability, the higher the risk of developing depressive symptoms is [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sclerosis (MS) is a chronic neurodegenerative disease that affects the motor and cognitive systems, increasing the risk of developing negative mental health outcomes, such as depressive symptoms [ 1 , 2 , 3 , 4 , 5 ]. To this end, previous research has found that approximately 25–50% of people with MS (pwMS) have some form of major depression [ 6 ] and that the higher the level of disability, the higher the risk of developing depressive symptoms is [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%